Prospects of Sustainable Development as an Alternative to the Orthodox Conception of Development: A Critical Analysis of the Nigerian Experience - Ojurongbe, Samuel Ayodele (Contemporary Journal of Applied Sciences, 2024)
This article set out to know the chances of Sustainable Development in Nigeria, as a substitute for the traditional view of Development. The paper attempted to examine the initial positives that welcomed Sustainable Development by examining relevant studies on Sustainable Development issues in a developing economy such as Nigeria, and analyzed the possibilities and impossibilities as well as its effectiveness over the original concept of Development. Among study findings were that the original perspective of Sustainable Development seemed to have been conceived to support and increase the gains of the Global North. In conclusion, it established that Nigeria has more challenges in the area of ensuring sustained human development which has become her alternative approach to development.